Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Video Animasi pada Materi Menghindari Gibah dan Melaksanakan Tabayun di SMP Negeri 8 Palopo - Hasdi, Khopipa; Kaharuddin; Hasriadi (South Sulawesi Education Development, 2025)
This research discusses the Influence of social media on students' learning behavior and motivation in Islamic History and Culture Learning at Al-Khaeriyah Murante Junior High School, Murante District, Suli Sub-district, Luwu Regency. The focus of this research is to determine the influence of social media on the learning behavior and motivation of eighth-grade students at MTs Al-Khaeriyah Murante. The type of research used is a quantitative approach. The population includes all eighth-grade students, and the sampling technique used was saturated sampling, meaning that the entire population was used as a sample, resulting in 32 students. Data was collected using questionnaires and then analyzed using simple regression analysis. The results of this study indicate that there is a significant negative influence of social media (X) on students' learning behavior (Y1) and motivation (Y2), as evidenced by the significance value of the hypothesis test for the learning behavior variable (0.00 < 0.05) and the student motivation variable (0.01 < 0.05). The negative t-test value (-4.076 and -3.517) indicates a negative relationship between the use of social media and students' learning behavior and motivation. The higher the use of social media, the lower the students' learning behavior and motivation in the Islamic history and culture subject. This study shows that the unwise and excessive use of social media can negatively affect students' learning behavior and motivation. This should be a concern for parents, teachers, and schools to increase supervision and education about the responsible use of social media. The influence of the social media variable (X) on learning behavior (Y1) is 35.6%, and the influence of the social media variable (X) on motivation (Y2) is 29.2%; the rest is influenced by other factors that were not examined in this study.